Trauma Recidivism Postdischarge Mortality: Important Differences Exist between the Adult and Geriatric Populations. Issue 7 (July 2019) - Gerrish, Ashley W.; Hamill, Mark E.; Locklear, Tonja M.; Bower, Katie L.; Lollar, Daniel I.; Faulks, Emily R.; Matos, Miguel; Nussbaum, Michael S.; Collier, Bryan R.
Trauma recidivists are a high-risk patient population. The effects of recidivism on Geriatric trauma mortality have not been investigated. Our hypothesis is that trauma recidivism is associated with high postdischarge mortality after the initial index admission in both the geriatric and adult trauma populations. The trauma registry of our Level I trauma center was queried for patients evaluated between 2008 and 2012. Patients were stratified adult (18–64) and geriatric (≥65) groups and matched with mortality data from the National Death Index. Unique patients were identified and recidivists flagged. Statistical analysis was performed based on characteristics from the index admission using nonparametric tests, and Kaplan–Meier curves were plotted to examine postdischarge mortality after index admission for recidivists. A total of 8716 records met inclusion criteria; 800 recidivist records were identified representing 369 unique patients. Recidivists presented between 2 and 7 times. Recidivists were more likely to be male, required ICU admission and mechanical ventilation, had a longer median length of stay, were less likely to discharge home, and had a higher postdischarge mortality. Stratifying into adult and geriatric groups demonstrated significant differences in injury severity, injury patterns, length of stay, race, gender, mechanism, and postdischarge mortality. Recidivists demonstrated a higher postdischarge mortality in both groups with the geriatric group approaching 46 per cent. Trauma recidivists represent an at-risk group with significantly higher postdischarge mortality. Group characteristics differ significantly between the adult and geriatric recidivist populations. Further research is needed to identify modifiable risk factors in these populations to minimize risks of morbidity and mortality.